Pertumbuhan Plantlet Anggrek Cattleya sp. dengan Perlakuan Benzyl Amino Purine pada Media Dasar Pupuk Daun Modifikasi - YUSWANTI, HESTIN; ASTAWA, I. N. G.; DEWI, N.N.A. MAYA (Agrotrop : Journal on Agriculture Science; Vol 4 No 2 (2014), 2015)
Growth of Plantlets of Cattleya Orchid on The Fooliar Fertilizer-Based Medium added with Benzyl Amino Purine. The aim of the current research was to investigate the appropriate concentrationof plant growth regulator BAP on the growth of Cattleya plantlet. The experiment was utilized a Randomized Completely Design with five treatments and six replications. The basal medium used was modification of foliar fertilizer of Growmore (trade mark) with addition of fish emulsion, Vitamin B1 and active charcoal. BAP concentration used as treatment were 0 ppm, 0.5 ppm, 1.0 ppm, 1.5 ppm and 2.0 ppm. Variables observed were height, leaf number, root number, root length, fresh weight and dry weight of plantlets. The result showed that concentration of 1 ppm BAP resulted in the highest value for plantlet height (5.67 cm), leaf number (4.67), root length (2.07 cm), fresh weight (0.36 g) and dry weight (0.043 g).
Keywords: Cattleya orchid; BAP; in vitro; plantlets